Uji In Vitro Aktivitas Imunomodulator Minyak Atsiri Serai Dapur (Cymbopogon citratus) terhadap Proliferasi Sel Limfosit Mencit - Gustria Ernis; Doni Notriawan; Dyah Fitriani; Elvira Yunita; Inta Cantika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the immunomodulatory activity of lemongrass essential oil on the proliferation of mouse lymphocyte cells in vitro. The method used is steam distillation to obtain citronella essential oil. Isolation of lymphocyte cells was obtained from the spleen organ of Swiss-Webster strain mice which was carried out aseptically. The lymphocyte cell proliferation test was carried out using the MTT Assay method and the absorbance was measured using an ELISA reader at 550 nm. The results showed that the lemongrass essential oil contained positive alkaloids, flavonoids, saponins, and steroids/triterpenoids with an essential oil yield of 0.043%. The higher the volatile oil concentration, the higher the Optical Density (OD) value obtained, but the OD increase at a 50 to 100 g/mL concentration was not significantly different. In conclusion, lemongrass essential oil has immunomodulatory activity against lymphocyte cell proliferation in mice tested in vitro. Keywords: Immunomodulator, Essential Oil, Lemongrass (Cymbopogon citratus), Immune System